Peran Guru dalam Mengembangkan Pembelajaran dengan Mengimplementasikan Kurikulum Merdeka di SMP Negeri 4 Jerowaru - Mustiari Ningsih; Meta Intan Kuswari; Lalu A. Hery Qusyairi (Pendidikan Al-Gafari, 2024)
Behind successful education, some teachers play a vital role in the continuity of education. These teachers are one of the components needed in line with government policy to provide education in all fields as widely as possible to educate the nation. Hence, the need for these teachers who meet the requirements and are sufficient in number is the necessity for procurement to be undertaken by road. This research aims to improve and unite schools to adapt to the current curriculum. With a problem formulation of how to plan the implementation of the independent curriculum, how to implement the independent curriculum, and finally how to evaluate the implementation of the independent curriculum. This research uses a qualitative descriptive approach, the subjects of this research are the principal, the head of curriculum, and several subject teachers, and the informants in this research are the research subjects themselves. The methods used in collecting data in this research were observation, interviews, and documentation. The validity of the data using source triangulation techniques and strategies is then analyzed using an interactive model consisting of data collection, data reduction, data presentation, and conclusion. The results of the research can conclude that the planning for implementing the independent curriculum begins by formulating it together with members of the educational unit and then implementing the independent curriculum. The key to the success of implementing this curriculum is that the final teacher evaluation is carried out to see to what extent the learning competencies have been achieved by the students who will later evaluated so that subsequent learning competencies are better.